Investigation of Gallium–Boron Spin‐On Codoping for poly‐Si/SiOx Passivating Contacts. Issue 12 (6th December 2021) - Truong, Thien N.; Le, Tien T.; Yan, Di; Phang, Sieu Pheng; Tebyetekerwa, Mike; Young, Matthew; Al-Jassim, Mowafak; Cuevas, Andres; Macdonald, Daniel; Stuckelberger, Josua; Nguyen, Hieu T.
Abstract : Spin‐on Doping In article number 2100653, Thien N. Truong, Josua Stuckelberger, Hieu T. Nguyen, and co‐workers explored the possibility of p‐type co‐doping poly‐Si/SiOx passivating contacts using the spin‐on method with different mixtures of Ga and B glass solutions.